PENGARUH METODE MIND MAPPING TERHADAP PEMAHAMAN POLA HIDUP BERSIH DAN SEHAT PADA ANAK USIA 4-5 TAHUN - Salsabila Adinda Putri; Muhammad Reza; Dewi Komalasari; Wulan Patria Saroinsong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Mind Mapping method on the understanding of clean and healthy lifestyles in children aged 4-5 years, especially in the aspect of personal hygiene which includes bathing, shampooing, brushing teeth, cleaning the nose, cutting nails, washing hands, cleaning ears, wiping after defecation and urination. The background of this study is based on the condition of understanding of clean and healthy lifestyles in the aspect of personal hygiene that has not developed optimally and is still routine without being based on understanding. This Mind Mapping method is used as a learning strategy to provide knowledge to children about clean and healthy lifestyles through the presentation of main concepts and simple branches, so that children are able to group, connect, and understand various aspects of personal hygiene in a structured manner. This study uses a quasi-experimental method with a design (nonequivalent Pretest-Posttest control group design) which was implemented at TK Negeri Pembina 2 Surabaya with two classes, namely class A1 as the experimental group and class A2 as the control group with a total of 15 children in each class. The results of the Mann Whitney U Test showed that in the initial test (Pretest) there was no significant difference between the two groups, whereas after being given Treatment there was a significant difference, where the experimental group experienced an increase in understanding of clean and healthy lifestyle patterns as indicated by the children's ability to recognize, group, and explain aspects of personal hygiene through Mind Mapping. Based on these results, it can be concluded that the Mind Mapping method has an effect on understanding clean and healthy lifestyle patterns in children aged 4-5 years..